EVALUASI PELAKSANAAN PEMBELAJARAN PAI PADA MADRASAH SWASTA UNGGULAN - Ahmad Sulthoni (el-hikmah, 2011)
This research goal is to discern the implementation of PAI educational at Private Madrasah, especially covering the characteristic of students, of teachers, tools and equipments, students’ learning motivation, and teaching preparation instrument to support the daily learning activities by teachers, students’ participation in classes and personal relationship conducted by teachers in learning activities, resulting to student achievement at Madrasah Ma’arif. This research is implementation evaluation research conducted using descriptive quantitative data approach using Stake Model. Data collected using questioner, observation, interviews, documented and analyzed with descriptive statistic approach. The result given using distributed table and pie chart. Analyzing technique used by this research is descriptive qualitative and quantitative. The result explain that in general students’ parents at four madrasah has been researched is a farm worker and secondary schools graduate, students’ learning motivation at four schools shows good measures. Over all teachers at four schools has a graduate; however, teaching preparation conducted by teachers at four schools has been running good. The availability of tools and equipments at four schools has been researched was not sufficient yet; however, the learning process conducted by teachers at four schools has been researched has been running good. The students’ participation at learning process at four schools has been researched conclude a low indicator; however, the personal relationship conducted by teachers and students has been running good. The students achievement at four schools has been researched fulfill the needs criteria and the academic achievement which resulting good attitudes at four schools has been researched show a good condition.